Complications of colonoscopy: common and rare—recognition, assessment and management - Zacharias P Tsiamoulos; Matthew Banks; Bhaskar Kumar; Nigel J Trudgill; Umair Kamran; William Waddingham (BMJ Open Gastroenterology)
An understanding of the potential complications of diagnostic lower gastrointestinal endoscopy is a necessary part of being an independent endoscopist. Creating a culture of safety and prevention of adverse events (AEs) should be part of routine endoscopy practice. Appropriate patient selection for procedures, informed consent, peri-procedure risk assessments and an inclusive team approach, all contribute to preventing AEs. Early recognition, prompt management and transparent communication with patients are essential for the holistic and optimal management of AEs. In this review, we discuss the complications of diagnostic lower gastro-intestinal endoscopy, including their recognition, treatment and prevention.